Burnout, work–life balance, and turnover intention: The mediating role of engagement - Fajriawan, Nazli; Dewi, Ni Putu Ayu Muspita (Review of Management, Accounting, and Business Studies, 2025)
In an era of rapid business change and intensifying global competition, effective human resource management is critical for sustaining organizational performance. Understanding factors that influence employee well-being, engagement, and retention has therefore become a key managerial concern. This study examines the effects of employee burnout and work–life balance on employee engagement and turnover intention, with a particular focus on the mediating role of employee engagement. The research was conducted at PT Ulun Danu Beratan Lestari, a hospitality organization in Bali, Indonesia. Using a quantitative approach, data were collected from 100 employees selected through purposive sampling from a population of 130 employees. Primary data were obtained via structured questionnaires, complemented by secondary data from organizational documents and relevant literature. The findings indicate that burnout has a positive relationship with employee engagement, while work–life balance also positively influences employee engagement. Burnout is found to significantly affect turnover intention, whereas work–life balance does not show a significant relationship with turnover intention. Furthermore, employee engagement does not have a significant effect on turnover intention and does not mediate the relationship between burnout and turnover intention, nor between work–life balance and turnover intention. These results suggest that employee engagement alone may not sufficiently explain turnover intentions in this organizational context. The study contributes to the literature by highlighting the complex relationships among burnout, work–life balance, and turnover intention, and suggests that future research should consider additional psychological or organizational factors to better explain employee turnover behavior.